The Legal Status of MUI Fatwas within the Indonesian Legal System - Wiwin, Wiwin (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2025)
This study examines the legal status of fatwas issued by the Indonesian Ulema Council (Majelis Ulama Indonesia, MUI) within Indonesia’s regulatory system. The research aims to identify the legal position of MUI fatwas in the Indonesian legal hierarchy and to analyze their juridical nature within the national legal framework. Employing normative legal research methods, this study adopts a statute-based and analytical approach, focusing on statutory regulations, legal doctrines, and relevant legal theories. The findings indicate that MUI fatwas do not constitute formal legislation and thus lack general binding legal force, as they are not issued by state-authorized bodies nor do they fulfill the formal requirements of written law. Nevertheless, MUI fatwas retain significant value as material legal sources and interpretive guidance, particularly for Indonesian Muslims and institutions such as Religious Courts. The nature of MUI fatwas is that of internal religious opinions non binding and applicable only to those who recognize the moral or religious authority of the MUI. Therefore, MUI fatwas are persuasive and moral-religious in character, rather than coercive like state enacted positive law.